Maximum Power Point Tracking Based on Sliding Mode Control - Nimrod Vázquez; Yuz Azaf; Ilse Cervantes; Eslí Vázquez; Claudia Hernández (International Journal of Photoenergy)
Solar panels, which have become a good choice, are used to generate and supply electricity in commercial and residential applications. This generated power starts with the solar cells, which have a complex relationship between solar irradiation, temperature, and output power. For this reason a tracking of the maximum power point is required. Traditionally, this has been made by considering just current and voltage conditions at the photovoltaic panel; however, temperature also influences the process. In this paper the voltage, current, and temperature in the PV system are considered to be a part of a sliding surface for the proposed maximum power point tracking; this means a sliding mode controller is applied. Obtained results gave a good dynamic response, as a difference from traditional schemes, which are only based on computational algorithms. A traditional algorithm based on MPPT was added in order to assure a low steady state error.